Identifying power brokers in climate change adaptation policy and decision making in Uganda - CGIAR Research Program on Climate Change, Agriculture and Food Security (2010)
The Advocates Coalition for Development and Environment (ACODE), a policy research and advocacy think-tank based in Uganda was approached to help organize a Focus Group Discussion (FGD) on power brokering in the climate change sector in Uganda. The objective of Date 30th August 2010 Start time 9:00am End time 1:00pm Stakeholders Present 1. Godber Tumushabe, Advocates Coalition for Development and Environment 2. Edith Kateme-Kasajja, National Planning Authority 3. Christine Nantongo, Environmental Alert 4. Paul Isabirye, Climate Change Unit (Ministry of Water and Environment) 5. Sara Namirembe, Katomba Group 6. Bashir Twesigye, Advocates Coalition for Development and Environment 7. Beatrice Anywar, Parliament of Uganda 8. Morrison Rwakakamba, Uganda National Chamber of Commerce and Industry 9. Sonja Vermeulen, Climate Change, Agriculture and Food Security. the FGD was to map out organizations, groups and individuals that influence climate change, agriculture and food security related policy making processes in the present (2010) setting.